The Impact of Inflation on Economic Growth in Indonesia in the 2019-2022 Period - Rolia Adelia; Cecep Hermana (LPPM Universitas Buddhi Dharma, 2026)
This study aims to analyze the effect of inflation on economic growth in Indonesia during the 2019-2022 period. This period was chosen because it represents unique economic dynamics, ranging from pre -pandemic stable conditions, contraction due to COVID-19, to economic recovery with external inflationary pressures. The research method uses a quantitative approach with annual time series secondary data sourced from the Central Statistics Agency (BPS) and Bank Indonesia. The results of the regression analysis show that inflation has a positive and significant effect on economic growth with a coefficient of determination (R Square) of 0.841, meaning that 84.1% of the variation in economic growth is influenced by inflation. The conclusion of this study confirms that inflation is an important variable that drives economic growth, so that appropriate fiscal and monetary policy management is needed to maintain price stability for sustainable growth.